Flexible bronchoscopy as a valuable tool in the evaluation of infants with stridor - KARADAĞ, BÜLENT TANER; ERDEM ERALP, ELA; GÖKDEMİR, YASEMİN (SPRINGER, 2013)
The aim is to determine clinical characteristics, flexible bronchoscopy (FB) findings including associated airway abnormalities and other conditions, treatment modalities and long term follow-up of children with congenital stridor. Medical records of children, who underwent FB for the evaluation of stridor between 1 January 2004 and 31 December 2009 were retrospectively reviewed. Demographic characteristics, symptoms and physical examination findings at presentation, FB findings, follow-up data including the time to resolution of symptoms and treatment modalities, presence of associated conditions were assessed. 109 children were enrolled to the study. Laryngomalacia was the most common etiology for stridor. Laryngomalacia was isolated in 37 patients and 54 patients had secondary airway lesions (SALs). Diagnoses other than laryngomalacia such as subglottic hemangioma, subglottic web, isolated tracheomalacia were found in 18 patients. In 90 % of patients, stridor resolved before 3 years of age without any surgical intervention and there was no significant difference in terms of the persistence of stridor between patients with isolated laryngomalacia and associated SALs. Duration of stridor was significantly longer in both patients with neurological abnormalities and reflux symptoms. Surgical procedure was performed in 19 of the patients. There is a high incidence of SALs in patients with laryngomalacia. FB is helpful for identifying anomalies requiring surgical treatment.
Keywords: Stridor; Laryngomalacia; Secondary airway lesions; Flexible bronchoscopy; SYNCHRONOUS AIRWAY LESIONS; GASTROESOPHAGEAL-REFLUX; LARYNGOMALACIA; CHILDREN; TRACHEOMALACIA; BRONCHOMALACIA; DISORDERS; ENDOSCOPY; ANOMALIES